Assessing Nitrosamine Migration from Drinking Water Contact Materials Using a Validated LLE-GC-MS Method - Beatriz Antunes; Andreia Videira; Ana Penetra; Vitor V. Cardoso; Rui N. Carneiro; Cristina M. M. Almeida (Molecules)
Nitrosamines (NAs) are toxic compounds associated with disinfection processes. Human exposure can occur through the hydraulic hoses and seals that are in contact with drinking water. This study develops and validates a chromatographic method to quantify 11 NAs in water leachates from four organic materials. The method is based on liquid–liquid extraction (LLE) followed by gas chromatography coupled with mass spectrometry (GC-MS). The method was validated by the application of several statistical tests, namely, linearity/working range, precision, trueness, and recovery tests. The GC-MS method showed a good linear range for all NAs with coefficients of determination (r2) higher than 0.9989, coefficients of variation of the method (CVm) lower than 2.5%, and PG < F (0.05; 1; N-3). The working range varies between 10 µg/L and 386.7 µg/L. The GC-MS method showed good precision under repeatability and reproducibility conditions with a relative standard deviation (RSD) lower than 12% and 10%, respectively. The GC-MS showed good trueness with a relative error lower than 20%. Matrix effects were significant, with recovery (Rec) values between 47% and 125% and an RSD lower than 20%. The limit of detection (LOD) and quantification (LOQ) ranged between 0.71 µg/L and 8.9 µg/L and between 2.3 µg/L and 29.8 µg/L, respectively. The method quantification limits (MQL) ranged from 0.0045 µg/L to 0.0378 µg/L. The sum of the MQL (0.2 µg/L) is lower than the reference limit of 0.3 µg/L for NAs in the leachates from the migration tests. Four organic materials were subjected to migration tests with demineralized and chlorinated water to assess their suitability for the water supply system. These materials met the NA specifications for use in the water network.